An Optimization Mechanism Intended for Static Power Reduction Using Dual-𝑉thTechnique - Rodolfo P. Santos; Gabriela S. Clemente; Abel Silva-Filho; Cristiano Araújo; Adriano Sarmento; Manoel Lima; Edna Barros (Journal of Electrical and Computer Engineering)
Power consumption reduction is a challenge nowadays. Techniques for dynamic and static power minimization have been proposed, but most of them are very time consuming. This work proposes an algorithm for reducing static power, which can be perfectly inserted in the conventional design flow for integrated systems considering an open source environment (open access infrastructure). The proposed approach, based on a Dual-Threshold technique, replaces part of the cells of the circuit by cells with a higher threshold voltage without resulting in timing violations in the circuit. The decision to replace a cell is based on timing estimates of the circuit modeling with the cell replacement, before it is actually replaced. The fact that only some cells are replaced every iteration results in a reduction of the runtime of the algorithm. Additionally, results showed a reduction in static power up to 39.28%, when applying the proposed approach in the ISCAS85 benchmark circuits.